The Effect Of Hydrogen Peroxide (H₂O₂) in Yoghurt (Lactobacillus bulgaricus and Streptococcus thermophilus) on Inhibiting the Growth of Streptococcus pyogenes - IDSAP Peramiarti; Rifqi Akmal Adrianto (Medical and Health Journal, 2026)
Yoghurt is a food product made from milk fermented with lactic acid bacteria (LAB), which provides various health benefits, including enhancing immunity through the production of lactic acid, hydrogen peroxide, diacetyl, and bacteriocins. Several studies have reported that LAB-fermented yoghurt can inhibit the growth of pathogenic bacteria. Streptococcus pyogenes is a gram-positive bacterium that forms chain like colonies, is small, round in shape, has a smooth surface, and produces grayish-white pigmentation on blood agar. S. pyogenes can cause respiratory infections such as pharyngitis, and skin infections such as impetigo, cellulitis, and erysipelas. This study aimed to investigate the role of hydrogen peroxide in yoghurt (L. bulgaricus and S. thermophilus) in inhibiting the growth of S. pyogenes. This was an experimental study using a post-test-only control group design. Bacterial colony counts were performed using a colony counter. A total of 60 samples were used, with three repetitions, two dilutions, and ten concentration groups (0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%), with 0% serving as the control. Data were analyzed using the Kruskal-Wallis test, followed by the Spearman Rho test. The results showed that yoghurt inhibited the growth of S. pyogenes, and the 30% yoghurt concentration, containing 0.32 mmol/L hydrogen peroxide, was the minimum inhibitory concentration. Kruskal-Wallis analysis showed significant differences among groups (p<0.05), and the Spearman Rho test indicated a significant correlation (p<0.05) between the variables.